On the anti-exhaustive inference of ya - Nicolae, Andreea C.; Sudo, Yasutada (Proceedings of the Amsterdam Colloquium, 2024)
Sudo 2014 analyzes the connective ya in Japanese as an inclusive disjunction that triggers two scalar inferences, (i) a conjunctive inference and (ii) an anti-exhaustive inference, based on alternatives involving other connectives. Sauerland et al. 2017 propose a competing analysis of (i) that is based on domain alternatives, but they make no claim about (ii). We report on an experiment with an inference task whose results indicate that ya does indeed trigger (ii) but it is not as robust as (i). We argue that this is problematic for Sudo’s (2014) analysis, but at the same time shows that Sauerland et al.’s (2017) analysis needs to be augmented with a mechanism for generating (ii). In order to account for the difference in robustness, we propose that (i) is a grammatically derived scalar inference, while (ii) is a pragmatically derived scalar inference.